Risk Factors of Anemia in Coastal Communities in Indonesia: A Review - Devi Savitri Effendy; Putu Ayu Sawitri; Sitti Herawati (Journal of Epidemiology and Health Science, 2025)
Background: Anemia remains a significant public health concern, particularly in coastal regions of Indonesia. Various factors, including dietary patterns, nutritional status, menstrual cycles, and socioeconomic conditions, contribute to the high prevalence of anemia among coastal populations. Objective: This study aims to review existing literature on anemia in coastal communities in order to identify associated risk factors, health impacts, and effective prevention strategies. Methods: This research employs a literature review approach by analyzing 20 Indonesian-language journal articles that focus on the prevalence, risk factors, and interventions related to anemia. The selected studies provide insights into both the causes and the efforts undertaken to address anemia in coastal areas. Results: The review indicates that poor nutritional status, unbalanced dietary intake, and limited health education are the primary contributors to anemia in coastal communities. Furthermore, educational initiatives and iron supplementation programs have demonstrated effectiveness in improving knowledge and reducing anemia prevalence. Conclusion: To effectively reduce the burden of anemia in coastal areas, community-based interventions are essential. These should include nutrition counseling, public health education, and enhanced access to iron-rich and nutritious foods. Keywords: Anemia, Coastal Communities, Nutritional Status, Health Education, Indonesia.